Surface modified fullerene electron transport layers for stable and reproducible flexible perovskite solar cells. (July 2018) - Song, Seulki; Hill, Rebecca; Choi, Kyoungwon; Wojciechowski, Konrad; Barlow, Stephen; Leisen, Johannes; Snaith, Henry J.; Marder, Seth R.; Park, Taiho
Abstract: We report flexible planar perovskite solar cells with robust electron-transport layers (ETLs) processed at low temperature. A poly(allylamine) (PAA; 0.08 wt%) solution was deposited on a C60 layer and heated at 150 °C for 60 s, resulting in the formation of an insoluble robust C60 –PAA electron-transport layer (ETL) on the flexible substrate. The flexible planar perovskite solar cell with the C60 –PAA ETL exhibited excellent properties with 83% efficiency retention (η = 15.2% without hysteresis) after 600 cycles of bending. This performance is superior to that of the flexible device with a C60 ETL fabricated without the use of PAA (65% efficiency retention; η = 9.8% with some hysteresis). Graphical abstract: fx1 Highlights: A modified fullerene-based electron transport layer is proposed for stable flexible perovskite device. A poly(allylamine) (PAA; 0.08 wt%) solution was deposited on a C60 layer to form a C60 -PAA. C60 –PAA electron-transport layer (ETL) is insoluble in perovskite precursor solution. Flexible planar perovskite solar cell with the C60 –PAA ETL exhibited excellent properties with 83% efficiency retention.